PFASs–restriction proposal commentary on ECHA’s Annex XV restriction report, proposal for a restriction, March 2023 - Klaus-Michael Wollin; Monika Batke; Georg Damm; Alexius Freyberger; Ursula Gundert-Remy; Aswin Mangerich; Jan G. Hengstler; Falko Partosch; Thomas Schupp; Anna Sonnenburg; Heidi Foth (Archives of Toxicology, 2023)

Long-term simulation of lead concentrations in agricultural soils in relation to human adverse health effects - Thomas Schupp; Georg Damm; Heidi Foth; Alexius Freyberger; Thomas Gebel; Ursula Gundert-Remy; Jan G. Hengstler; Aswin Mangerich; Falko Partosch; Claudia Röhl; Klaus-Michael Wollin (Archives of Toxicology, 2020)
Lead (Pb) exposure of consumers and the environment has been reduced over the past decades. Despite all measures taken, immission of Pb onto agricultural soils still occurs, with fertilizer application, lead shot from hunting activities, and Pb from air deposition representing major sources. Little is known about the intermediate and long-term consequences of these emissions. To gain more insight, we established a mathematical model that considers input from fertilizer, ammunition, deposition from air, uptake of Pb by crops, and wash-out to simulate the resulting Pb concentrations in soil over extended periods. In a further step, human oral exposure by crop-based food was simulated and blood concentrations were derived to estimate the margin of exposure to Pb-induced toxic effects. Simulating current farming scenarios, a new equilibrium concentration of Pb in soil would be established after several centuries. Developmental neurotoxicity represents the most critical toxicological effect of Pb for humans. According to our model, a Pb concentration of ~ 5 mg/kg in agricultural soil leads to an intake of approximately 10 µg Pb per person per day by the consumption of agricultural products, the dose corresponding to the tolerable daily intake (TDI). Therefore, 5 mg Pb/kg represents a critical concentration in soil that should not be exceeded. Starting with a soil concentration of 0.1 mg/kg, the current control level for crop fields, our simulation predicts periods of ~ 50 and ~ 175 years for two Pb immission scenarios for mass of Pb per area and year [scenario 1: ~ 400 g Pb/(ha × a); scenario 2: ~ 175 g Pb/(ha × a)], until the critical concentration of ~ 5 mg/kg Pb in soil would be reached. The two scenarios, which differ in their Pb input via fertilizer, represent relatively high but not unrealistic Pb immissions. From these scenarios, we calculated that the annual deposition of Pb onto soil should remain below ~ 100 g/(ha × a) in order not to exceed the critical soil level of 5 mg/kg. We propose as efficient measures to reduce Pb input into agricultural soil to lower the Pb content of compost and to use alternatives to Pb ammunition for hunting.

High exposure to inorganic arsenic by food: the need for risk reduction - Ursula Gundert-Remy; Georg Damm; Heidi Foth; Alexius Freyberger; Thomas Gebel; Klaus Golka; Claudia Röhl; Thomas Schupp; Klaus-Michael Wollin; Jan Georg Hengstler (Archives of Toxicology, 2015)

Manufactured nanomaterials: categorization and approaches to hazard assessment - Thomas Gebel; Heidi Foth; Georg Damm; Alexius Freyberger; Peter-Jürgen Kramer; Werner Lilienblum; Claudia Röhl; Thomas Schupp; Carsten Weiss; Klaus-Michael Wollin; Jan Georg Hengstler (Archives of Toxicology, 2014)

PARP-1 expression and activity in primary human lung cells - Mohamed Ahmad; Abdelrahman Torky; Felix Glahn; Robert J. Scheubel; Heidi Foth (Archives of Toxicology, 2011)

Cadmium, cobalt and lead cause stress response, cell cycle deregulation and increased steroid as well as xenobiotic metabolism in primary normal human bronchial epithelial cells which is coordinated by at least nine transcription factors - Felix Glahn; Wolfgang Schmidt-Heck; Sebastian Zellmer; Reinhard Guthke; Jan Wiese; Klaus Golka; Roland Hergenröder; Gisela H. Degen; Thomas Lehmann; Matthias Hermes; Wiebke Schormann; Marc Brulport; et al. (Archives of Toxicology, 2008)

The role of the queen mandibular gland pheromone in honeybees (Apis mellifera): honest signal or suppressive agent? - Katrin Strauss; Holger Scharpenberg; Robin M. Crewe; Felix Glahn; Heidi Foth; Robin F. A. Moritz (Behavioral Ecology and Sociobiology, 2008)

Arachidonic acid pathway activates multidrug resistance related protein in cultured human lung cells - Abdelrahman Torky; Anja Raemisch; Felix Glahn; Heidi Foth (Archives of Toxicology, 2008)

Non-destructive micromethod for MRP1 functional assay in human lung tumor cells - Ekkehard Stehfest; Abdelrahman Torky; Felix Glahn; Heidi Foth (Archives of Toxicology, 2006)

Expression of lung resistance-related protein, LRP, and multidrug resistance-related protein, MRP1, in normal human lung cells in long-term cultures - Thomas Lehmann; Abdel-Rahman Wageeh Torky; Ekkehard Stehfest; Stefan Hofmann; Heidi Foth (Archives of Toxicology, 2005)

Expression of cytochrome P450 2E1 in normal human bronchial epithelial cells and activation by ethanol in culture - Dorothee Runge; Thomas Stock; Thomas Lehmann; Christiane Taege; Ulrike Bernauer; Donna Beer Stolz; Stefan Hofmann; Heidi Foth (Archives of Toxicology, 2001)

Nicotine metabolism in isolated perfused lung and liver of phenobarbital- and benzoflavone-treated rats - Heidi Foth; Helmut Looschen; Hartmud Neurath; Georg F. Kahl (Archives of Toxicology, 1991)

Comparison of benzo(a)pyrene metabolism in isolated perfused rat lung and liver - Michael Mollire; Heidi Foth; Regine Kahl; Georg F. Kahl (Archives of Toxicology, 1987)